Multiple magnet ingestion in children: presentation, diagnostics and management - Daškevičiūtė, Aurelija; Kolevinskaitė, Smiltė; Trainavičius, Kęstutis (Lietuvos chirurgija, 2017)
Introduction Although most ingested foreign bodies pass innocuously through the gastrointestinal tract, multiple magnets can lead to serious injury resulting from the attraction of the magnets across tissues. Objectives To identify the clinical presentation, diagnostics and management of magnet ingestions. Methods A retrospective review of magnet ingestions treated between January 2011 and January 2016 was developed. Patients’ demographics, clinical information, radiologic images and surgical records were obtained. Results 7 cases of multiple magnet ingestions were identified. Three patients presented with magnets located in the stomach. All of those patients were asymptomatic; two of them underwent endoscopic removal. Three patients presented with magnets located in the small intestine; two of them had abdominal pain and underwent laparoscopic retrieval. Spontaneous evacuation of magnets occurred in two cases. One asymptomatic patient had magnets located in the colon; enema was performed and evacuation of magnets occurred. Conclusion Cases of multiple magnets ingestion require aggressive management as migration of the objects might result in complications and greater morbidity.